More than Fabric Motifs: Changed Meaning of Nsibidi on the Efik Ukara Cloth - Ajibade, Babson; Ekpe, Esther; Bassey, Theodora (Richtmann Publishing, 2012)
Among the Ejagham people of the Cross River, extending from the Cameroon to Nigeriaâ€™s Cross River Sate, the ukaracloth and nsibidi visual signs are very critical aspects of history, religion and general cultural worldviews. While the ukara cloth isprominent among initiates of the Ejaghamâ€™s many Leopard Societies, the nsibidi is a visual language, unspoken but forming themain body of motifs on the ukara fabric design. As a traditional African written language peculiar to the Ejagham peoples,Carlson (2003: 225) has suggested that nsibidi can â€œadapt to new historical circumstances and cultureâ€ when transmitted to non-Ejagham societies. Using evidence from fieldwork in villages in five local government areas where Efik clans are located inCross River State, this study sort to find out if the meanings of key nsibidi signs have changed or adapted when transmitted intoa non-Ejagham cultural space in Calabar. The study found out that the transmission from the Ejagham culture to that of the Efikhas brought on adaptations and changes in the meaning of nsibidi. And, that through its use in the design of the ukara fabric ofthe Ekpe society, nsibidi has maintained its relevance among the Efik for many centuries because of its ability to adapt to newsocial and cultural situations, while remaining true to its original identity.